Analysis of the Contents of the Major Free Chinese Learning Websites - Chang, Lihong (IJRDO - Journal of Social Science and Humanities Research, 2019)
This paper offers an analysis of the current major Chinese language learning websites with free content. It first compares the websites and highlights some of their strengths and weaknesses. Second, it offers some suggestions for their future development. The study concludes that Chinese language learning websites should provide more practical free online resources for non-native speakers to learn the Chinese language in the easiest, fast, and most efficient way.